Exchange and provision of information in the field of tax administration and prevention of tax evasion - Čunderlík, Ľubomír; Szakács, Andrea (Institutiones administrationis, 2023)
The exchange and provision of information on taxpayers generally pursue different objectives. According to the provisions of tax law, the main purpose of obtaining information on taxpayers was to implement effective tax administration. Subsequently, other tasks have been added to this objective, including prevention of tax evasion, tax avoidance and related tax crime detection and investigation. The provision and exchange of information between the tax administration authorities and other legal entities, especially the national supervisory authority or national central bank, is subject to a strict regulatory regime, based on an explicit legal mandate to utilise the information. The reason is that the subject of the provision and exchange is often information that has a special secrecy protected by the law, such as banking secrecy, professional secrecy or protected information regarding securities. The authors identify and analyse the legal regime for providing information for the purposes mentioned, especially in the conditions of the Slovak Republic. The legal regime in the Slovak Republic is also more or less affected by legal acts adopted at global (OECD) level and EU level, so the authors take into account, to some extent, these legal acts when dealing with the automatic exchange of tax information between the tax administration of EU and non-EU member states. In this context, the authors differentiate according to whether the provision of information takes place under vertical or horizontal institutional relations. Following that, the aim of the paper is to identify how the related authorities/persons interact in horizontal institutional relations and vertical institutional relations.